Pure Islamic rationalization of the Muhammadiyah congregation in the hills and south coast of Watulimo-Trenggalek - Azis, Hamzah Nur; Sudarso, Sudarso (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2023)
The diversity of people of the hills and the coast of South Java has a different style from the people of the coast of North Java. This research aims to explore how Muhammadiyah as a puritan Islamic organization can develop and grow during the culture and habits of the hill community as well as the South coast of Watulimo-Trenggalek, and how the social behavior of Muhammadiyah members and congregation of the Watulimo Branch. This study used a qualitative method with Max Weber's social theory approach regarding changes in society to become modern which looks different between people in the East and West regions. The results showed the success of the Muhammadiyah movement in spreading its teachings in Watulimo using two approaches. The first is by the study route that has been adapted to the cultural context of the south coast community, and the second is by formal education. This study concludes that these two approaches led to the emergence of four Muhammadiyah jemaah groups in Watulimo.